A polarizing plate composite precursor, a polarizing plate, and a method for producing the same

CN119882102BActive Publication Date: 2026-10-23YANGTZE OPTICAL FIBRE & CABLE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411963483.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2026-10-23
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

[0004]针对现有技术的缺陷,本申请的目的在于提供一种偏振片复合母材、偏振片及其制备方法,旨在解决现有偏振片制备过程技术难度高、制备周期长、制备效率低以及存在风险的问题

Benefits of technology

本申请提供一种偏振片复合母材、偏振片及其制备方法,当基材的粘度处于其能够被拉伸的粘度范围时,若含金属掺杂物处于半熔融或熔融状态,则在对基材拉伸时,基材发生形变,与此同时基材变形对金属掺杂物产生挤压作用,在此作用下半熔融或熔融状态下的金属掺杂物相应发生形变。故本申请能够基于上述偏振片复合母材制备偏振片。相比现有拉伸还原法中掺杂金属卤化物,先拉伸后还原的方式,本申请则直接对复合母材拉伸即可得到偏振结构,无需进行还原反应,技术难度低、制备周期短、制备效率高,且直接采用含金属掺杂物避免了氢气在高温高压下参与反应,大大避免了制备过程存在的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119882102B_ABST
    Figure CN119882102B_ABST
Patent Text Reader

Abstract

The application belongs to the field of optical communication devices, and specifically discloses a polarizer composite master material, a polarizer and a preparation method thereof, which comprises a base material and metal dopant, the metal dopant is dispersedly distributed in the base material, the metal dopant comprises at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle, the metal-containing composite rod comprises a sub-metal rod, the base material is a stretchable material, and the material of the base material and the metal dopant is selected to satisfy the following condition: when the viscosity of the base material is in a viscosity range in which the base material can be stretched, the metal material in the metal dopant is in a semi-melted or melted state. Through the application, the controllability, stability and safety of polarizer preparation are improved, the preparation period is shortened, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of optical communication devices, and more specifically, relates to a polarizer composite matrix, a polarizer, and a method for preparing the same. Background Technology

[0002] Traditional polarizers are generally polarizing prisms made of crystal birefringence (such as calcite), represented by GranThompson and GranTyler prisms. These polarizers have the advantages of high extinction ratio and transmittance, but they are expensive, bulky, and their resistance to light damage is limited due to the use of adhesives. Polarizing beam splitters (PBS) are made by satisfying Brewster's law, but they are also expensive and sensitive to the angle of incident light. Polarizers composed of two ZK3 flat glass plates sandwiching a sodium nitrate crystal can generate linearly polarized light using the principle of scattering, but this structure has poor stability. Metal wire grid polarizers have limited extinction ratios, and resin polarizers made of polyvinyl alcohol (PVA) are not heat-resistant.

[0003] Until the 1990s, Corning produced commercial polarizers with high extinction ratio, high transmittance, high light reception angle, and high weather resistance. These polarizers were manufactured using the stretching reduction method. To date, the stretching reduction method is the mainstream manufacturing method for polarizers used in optical communication devices—free-space isolators. It mainly consists of five manufacturing processes: glass melting, glass heat treatment, glass stretching, glass processing, and glass reduction. The manufacturing process is complex and challenging, involving numerous steps. Taking the glass melting and stretching processes as examples, the melting process mainly involves incorporating metal particles such as silver and copper into the glass matrix. For example, silver halides (AgCl, AgBr, etc.) are typically incorporated into the glass. The glass matrix is ​​generally a weakly phase-separated borosilicate glass to facilitate the precipitation of silver halide particles. Excessive silver halide doping leads to glass devitrification and reduced transmittance. Insufficient silver halide doping reduces the extinction ratio performance of the polarizer. Therefore, it is necessary to reasonably control the amount of silver doped. Meanwhile, silver exhibits color-developing ability in ions, which places high demands on the quality of phase-separated glasses. Stretching, a key process for controlling the microstructure—stretching spherical shapes into rod / needle shapes—directly affects the working wavelength corresponding to the extinction ratio and the angular deviation of the polarization axis. Therefore, parameters such as tensile force, temperature, and viscosity need to be strictly controlled to stably prepare high-performance products within a narrow parameter range. Looking at the entire preparation process of the stretching reduction method, it is characterized by high technical difficulty, long preparation cycle, low preparation efficiency, and the presence of hydrogen gas in the reduction stage under high temperature and pressure, which carries certain risks. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the purpose of this application is to provide a polarizer composite master material, a polarizer and its preparation method, which aims to solve the problems of high technical difficulty, long preparation cycle, low preparation efficiency and risks in the existing polarizer preparation process.

[0005] To achieve the above objectives, in a first aspect, this application provides a polarizer composite master material, comprising: a substrate and a metal dopant; The metal dopant is dispersed in the substrate; the metal dopant includes at least one of metal rods, metal composite rods, metal spheres, or metal particles; the metal composite rod includes a sub-metal rod; The substrate is a stretchable material, and the selection of the substrate and the metal dopant material satisfies the following conditions: when the viscosity of the substrate is within its stretchable viscosity range, the metal material in the metal dopant is in a semi-molten or molten state.

[0006] It is understandable that when the viscosity of the substrate is within its stretchable viscosity range, if the metal dopant is in a semi-molten or molten state, the substrate will deform during stretching. Simultaneously, the substrate deformation exerts a compressive effect on the metal dopant, causing the semi-molten or molten metal dopant to deform accordingly, generating corresponding nanorods. Therefore, this application can prepare polarizers based on the aforementioned polarizer composite substrate. Compared to the existing stretching-reduction method involving metal halide doping followed by stretching and then reduction, this application directly stretches the composite substrate to obtain the polarization structure without a reduction reaction. This method is less technically demanding, has a shorter preparation cycle, and higher preparation efficiency. Furthermore, the direct use of metal dopant avoids the participation of hydrogen in the reaction under high temperature and pressure, significantly mitigating the risks associated with the preparation process.

[0007] Furthermore, in existing stretching-reduction methods, a reduction reaction is performed after stretching, which reduces the volume of the structure after reduction and creates microscopic pores in the stretched structure, causing uncertainty in the performance control of the polarizer and potentially affecting the long-term reliability of the polarizer. In contrast, this application does not require a subsequent reduction reaction after stretching, thus avoiding further changes to the internal morphology of the stretched structure and greatly improving the long-term reliability of polarizer preparation and use.

[0008] In one example, the metal material in the metal-containing dopant accounts for less than 20% by weight in the composite matrix. Preferably, it is 0.05% to 10%.

[0009] It should be noted that the weight percentage of the metal material in the composite matrix determines the extinction ratio performance of the polarizer and affects its transmittance performance. When the weight percentage is too small, it is difficult to prepare a polarizer with a high extinction ratio ≥50dB. For polarizers with a small working bandwidth (center value ±20nm), a metal percentage in the composite matrix is ​​preferably ≥0.05%. Different working wavelengths require metal nanorods with different aspect ratios. If the weight percentage is too small, it is also difficult to prepare a polarizer with a large working bandwidth (compared to the aforementioned small working bandwidth). For polarizers with a large working bandwidth, a metal percentage in the composite matrix is ​​preferably ≥0.2%. When the weight percentage is too large, considering the scattering and absorption of light by the metal, it will affect the transmittance performance of the polarizer. Therefore, the weight percentage of the metal material in the composite matrix is ​​less than 20%, preferably ≤10%. Therefore, to prepare a polarizer with excellent comprehensive performance such as high extinction ratio and high transmittance, the weight percentage of the metal material in the composite matrix can preferably be in the range of 0.05%~10%.

[0010] In one example, the diameter of the metal rod is in the range of A. 10 -5 mm~A 10 -1 mm; preferably, the diameter of the metal rod is in the range of A. 10 -3 mm~A 10 -2 mm, where A is the thickness or diameter of the substrate, and the unit of the value is mm; The diameter range of the sub-metal rod is A. 10 -4 mm~A 10 1 mm; preferably, the diameter range of the sub-metal rod is A. 10 -2 mm~A 10 -1 mm; The metal sphere is a nano-metal sphere; preferably, the diameter of the nano-metal sphere is in the range of 5 nm to 500 nm. The metal particles are nano-sized metal particles.

[0011] It should be noted that the diameters of the metal rods and sub-metal rods, as well as the sizes of the metal spheres and metal particles, all determine the final size and / or aspect ratio of the metal material when stretched into nanorods. By defining these dimensions, it is possible to ultimately obtain the corresponding polarizers through stretching.

[0012] In one example, the aspect ratio of the metal rod is greater than or equal to 1.5; preferably, the aspect ratio is in the range of 2 to 100. The aspect ratio of the sub-metal rod is greater than or equal to 1.5; preferably, the aspect ratio is in the range of 2 to 100.

[0013] More preferably, in this application, the metal rod and the sub-metal rod can be selected with different aspect ratios. Metal rods or sub-metal rods with different aspect ratios can be combined and stretched in the composite matrix to produce nanorods with different aspect ratios. The working bandwidth of the polarizer depends on the aspect ratio of the nanorods. Therefore, by using the composite matrix provided in this application, the working bandwidth of the polarizer can be broadened and controlled by controlling the aspect ratio of the metal rod or the sub-metal rod.

[0014] In one example, the metal spheres are dispersed in the substrate as individual metal spheres and / or as assemblies of metal spheres; The metal particles are dispersed in the substrate as individual metal particles and / or as combinations of multiple metal particles.

[0015] It is understandable that by controlling the size of metal spheres or metal particle assemblies, nanorods with different aspect ratios can be obtained.

[0016] In one example, the substrate has a plurality of through holes, and at least one metal dopant is placed in one of the through holes.

[0017] Considering the difficulty of placing metal dopants into the substrate, at least one metal dopant can be placed in a single through-hole. When the metal dopant is a metal rod or a metal composite rod, the metal rod or metal composite rod can be inserted into a single through-hole as a whole or in segments.

[0018] In one example, the sizes of the metal dopants in the substrate may be the same or not exactly the same.

[0019] More preferably, considering the operating wavelength of the polarizer, if its operating wavelength is wide, the polarizer needs to contain nanorods with a wide range of different aspect ratios; as the aspect ratio increases, the operating wavelength shifts to higher wavelengths. Based on the above requirements, nanorods with the same or slightly different sizes containing metal dopants can be designed.

[0020] In one example, the metal-containing composite rod includes: at least one set of nested composite structures; each set of composite structures includes several sub-metal rods and a preset substrate enclosing the sub-metal rods; preferably, a core rod is disposed in the middle of the innermost composite structure; the preset substrate and the core rod are made of the same material as the substrate; more preferably, the substrate is made of glass; or, the metal-containing composite rod includes: a core rod and several sub-metal rods embedded inside the core rod, the core rod being made of the same material as the substrate; more preferably, the substrate is made of glass. And / or the sub-metal rod accounts for less than 50% of the mass of the metal-containing composite rod; And / or the softening point of the substrate is in the range of 600℃ to 1500℃.

[0021] It should be noted that when the metal-containing composite rod is composed of a sub-metal rod, a core rod, and a pre-defined substrate encapsulating the sub-metal rod, when the diameter of the metal-containing composite rod is comparable to that of the metal rod, the diameter of the sub-metal rod inside is smaller than that of the metal rod, making it easier to stretch. When using a metal-containing composite rod, the sub-metal rod inside is thinner. When stretching the composite parent material into a polarization structure, the thinner sub-metal rod will be easier to stretch into a nanorod, making it easier to prepare a polarizer.

[0022] If the mass percentage of the sub-metal rod in the aforementioned metal dopant is too large, the aforementioned metal dopant is not suitable for being stretched alone; the mass percentage of the sub-metal rod is controlled within a suitable range so that it can be stretched to a suitable size before being placed into the substrate.

[0023] It is understandable that the softening point of the substrate needs to be compatible with the semi-melting or melting point of the metal dopant so that the composite base material composed of the two can be stretched to obtain a polarized structure. Since the semi-melting or melting temperature of the metal material is relatively high, this application needs to select a substrate with a relatively high softening point to match it.

[0024] Secondly, this application provides a polarizer, which is obtained by stretching a composite base material described in the first aspect or any example of the first aspect; when stretching the composite base material, the viscosity of the substrate is within the viscosity range that it can be stretched, and the metal material in the metal dopant is in a semi-molten or molten state.

[0025] Thirdly, this application provides a stretching method for the polarizer described in the second aspect above, wherein the viscosity range of the substrate is controlled to be 10 when stretching the composite base material. 2 mooring~10 13 Po, preferably with a substrate viscosity of 10 4 mooring~10 10 The tension is applied within the range of 10MPa to 300MPa, and the discharge speed is controlled within the range of 10mm / min to 1000mm / min.

[0026] It should be noted that, due to the increased softening point range of the stretched substrate (600℃~1500℃), the corresponding viscosity range for stretching is 10. 2 mooring~10 13Furthermore, tensile tension is a key parameter for controlling the microstructure. The applied tension range is 10MPa to 300MPa, and the tension is adjusted according to the size of the stretched material within this range. As the tension increases, the aspect ratio increases. Due to the tendency of metallic materials to spherize under the influence of surface tension, the aspect ratio exhibits shrinkage. At this point, a high discharge speed can reduce shrinkage; therefore, a discharge speed greater than 10mm / min is preferred. However, excessively high discharge speeds result in poor stretching stability. Considering stability, the discharge speed should not exceed 1000mm / min.

[0027] Fourthly, this application provides a method for preparing the polarizer composite substrate described in the first aspect or any example of the first aspect, comprising: Provide base materials; A metal-doped material is provided; the metal-doped material includes at least one of a metal rod, a metal-containing composite rod, a metal sphere, or a metal particle; the metal-containing composite rod includes a sub-metal rod. The metal dopant is placed into a substrate to obtain a composite base material; the substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within its stretchable viscosity range, the metal material in the metal dopant is in a semi-molten or molten state.

[0028] In one example, when the metal dopant is a metal rod or a metal composite rod, the insertion is performed by drilling; preferably, the metal composite rod is stretched and then inserted into the substrate by drilling. When the metal dopant is a metal sphere or metal particle, the implantation is performed by injection. When the implantation method is ion beam implantation, the target material is at least one of metals such as silver, gold, and copper, and the implantation is performed on both sides or selectively on a specific area. The implantation energy is greater than or equal to 10 MeV, and the gas pressure range during implantation is 0.01 Pa to 1 Pa. Preferably, the area of ​​selective implantation is 0.01 mm². 2 ~10mm 2 The interval between the implanted regions is 0.01Amm to 5Amm, where A is the thickness or diameter of the substrate, and the unit of the value is mm; more preferably, when the implantation method is ion beam implantation, the thickness or diameter of the substrate is preferably 0.01mm to 5mm.

[0029] It should be noted that when the metal composite rod is stretched and then inserted, the number of stretching cycles required to prepare the polarizer using the metal composite rod is greater than the number of stretching cycles required for the composite base material using the metal rod. Therefore, the range of aspect ratio of the sub-metal rod used in the metal composite rod can be wider than the range of aspect ratio of the metal rod in the aforementioned embodiment, and it is easier to prepare the polarizer.

[0030] In one example, when the insertion is performed by drilling, holes are drilled inside the substrate along the stretching direction of the substrate.

[0031] More preferably, when the direction of the via is consistent with the direction of the substrate stretching, the metal dopant is more easily stretched into a nanorod, which can improve the control accuracy of the polarizer's transmission axis (i.e., the long axis of the nanorod).

[0032] Overall, the technical solutions conceived in this application have the following beneficial effects compared with the prior art: This application provides a polarizer composite substrate, a polarizer, and a method for preparing the same. When the viscosity of the substrate is within its stretchable viscosity range, if the metal dopant is in a semi-molten or molten state, the substrate deforms during stretching. Simultaneously, this deformation exerts a compressive effect on the metal dopant, causing it to deform accordingly. Therefore, this application can prepare polarizers based on the aforementioned polarizer composite substrate. Compared to existing stretching-reduction methods that involve doping with metal halides and then stretching followed by reduction, this application directly stretches the composite substrate to obtain the polarization structure without a reduction reaction. This method is less technically demanding, has a shorter preparation cycle, and higher efficiency. Furthermore, the direct use of the metal dopant avoids the participation of hydrogen in the reaction under high temperature and pressure, significantly mitigating the risks associated with the preparation process.

[0033] This application provides a polarizer composite base material, a polarizer, and a method for preparing the same. In existing stretching-reduction methods, a reduction reaction occurs after stretching, resulting in a reduction in the structural volume and the presence of microscopic pores in the stretched structure. This leads to uncertainty in the performance control of the polarizer and may affect its long-term reliability. In contrast, this application eliminates the need for a reduction reaction after stretching, thus preventing further alteration of the internal morphology of the stretched structure and significantly improving the long-term reliability of the polarizer's preparation and use. This application optimizes the base material preparation and stretching process while meeting product performance requirements, reducing the three steps of melting, crystallization, and reduction. This increases the safety of the entire polarizer preparation process, improves preparation efficiency, and reduces energy consumption.

[0034] This application provides a polarizer composite matrix, a polarizer, and a method for preparing the same. The aspect ratio of the metal rod and the metal composite rod in the metal dopant can be selected, and the size of the metal sphere and the metal particles can be adjusted. Therefore, the working bandwidth of the stretched polarizer can be controlled based on the size of the metal dopant. Compared with the existing stretching reduction method where the aspect ratio changes more randomly, the working bandwidth of the polarizer in this application is more adjustable.

[0035] This application provides a polarizer composite substrate, a polarizer, and a method for preparing the same. When a metal-containing composite rod is used, the distribution of the sub-metal rods in the substrate will be more dispersed and uniform, and the sub-metal rods will be finer. This can improve the uniformity of the distribution of metal materials in the polarizer, resulting in more uniform polarizer performance and easier preparation into nanorods, thus providing higher controllability. Attached Figure Description

[0036] Figure 1(a) is a first structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 1(b) is a second structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 1(c) is a third structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 1(d) is a fourth structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 1(e) is a fifth structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 2 This is a flowchart of the first preparation method of the polarizer composite master material provided in the embodiments of this application; Figure 3(a) is a cross-sectional view of the metal composite rod contained in the polarizer composite base material provided in the embodiment of this application; Figure 3(b) is a schematic cross-sectional view of the first type of polarizer composite material containing a metal composite rod provided in the embodiments of this application; Figure 3(c) is a second cross-sectional schematic diagram of the polarizer composite base material containing a metal composite rod provided in the embodiments of this application; Figure 3(d) is a schematic diagram of the third cross section of the polarizer composite base material containing a metal composite rod provided in the embodiments of this application; Figure 3(e) is a fourth cross-sectional schematic diagram of the polarizer composite base material containing a metal composite rod provided in the embodiments of this application; Figure 3(f) is a fifth cross-sectional schematic diagram of the polarizer composite base material containing a metal composite rod provided in the embodiments of this application; Figure 4 This is a flowchart of the second preparation method of the polarizer composite master material provided in the embodiments of this application; Figure 5(a) is a sixth structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 5(b) is a seventh structural diagram of the polarizer composite base material provided in the embodiments of this application; Figure 6 This is a schematic diagram of the eighth structure and preparation process of the polarizer composite master material provided in the embodiments of this application; Figure 7 This is a flowchart of the third preparation method of the polarizer composite master material provided in the embodiments of this application; Figure 8 This is a schematic diagram of the stretching furnace provided in an embodiment of this application; Figure 9 This is a schematic diagram of the microstructure of the polarizer obtained by stretching according to an embodiment of this application.

[0037] In all the accompanying drawings, the same reference numerals are used to denote the same elements or structures, wherein: 10 is a substrate, 20 is a metal rod, 21 is a core rod, 22 is a sub-metal rod, 23 is a pre-designed substrate enclosing the sub-metal rod, 231 is a first sleeve, 232 is a second sleeve, 233 is a third sleeve, 30 is a metal ball, 40 is a hole, 50 is a metal particle, 61 is the front side of the substrate, 62 is the back side of the substrate, 70 is an ion beam, 80 is a feeding area, 81 is a stretching area, 82 is a discharge area, 100 is a nanorod, and 200 is a stretched substrate. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0039] The embodiments of this application are described below with reference to the accompanying drawings.

[0040] It should be noted that the theoretical basis for the polarization effect of polarizers lies primarily in the interaction between the metal nanoparticles in the glass matrix and the electric vector of the light wave, resulting in collective resonant absorption by a large number of free electrons within the metal particles. When the electric vector direction of the incident light wave is parallel to the long axis of the rod-shaped metal particles, this portion of the incident light is absorbed by the oscillation of the free electrons within the metal particles, converting light energy into heat energy. Conversely, when the electric vector direction of the incident light wave is perpendicular to the long axis of the rod-shaped metal particles, this portion of the light passes through. Ultimately, the incident natural light is transformed into linearly polarized light after passing through the polarizing glass.

[0041] Furthermore, the polarization effect of the aforementioned polarizer is closely related to the shape and size of the nanoparticles. The controllability of the regularly arranged array of metal nanoparticles plays a decisive role in the polarization performance of the polarizing glass.

[0042] The main objective of this application is to provide a polarizer composite base material for preparing polarizers based on the composite base material; and to provide a new method for preparing polarizers, which simplifies the preparation process, shortens the preparation cycle, improves production efficiency, reduces preparation energy consumption, and increases the controllability and stability of polarizer preparation.

[0043] Specifically, the polarizer composite master material provided in this application includes: a substrate and a metal dopant; the metal dopant is dispersed in the substrate; the metal dopant includes a metal rod (see...). Figures 1(a) to 1(e) ), metal-containing composite rods (see) Figures 3(a) to 3(f) ), metal spheres (see Figure 5(a), Figure 5(b)) or metal particles (see Figure 6 At least one of the following.

[0044] More preferably, the substrate is a stretchable material, and the selection of the substrate and the metal dopant material satisfies the following conditions: when the viscosity of the substrate is within the viscosity range that allows it to be stretched, the metal in the metal dopant is in a semi-molten or molten state, so as to ensure that the microstructure of the composite parent material can be controlled during stretching, and to ensure that an ideal aspect ratio nanorod is obtained.

[0045] More preferably, the above-mentioned substrate is a material with a light transmittance of ≥80% and a softening point range of 600℃~1500℃; those skilled in the art usually select glass that meets the above requirements as the substrate.

[0046] The solutions provided in the embodiments of this application will be described in detail below with reference to the first to fourth types of embodiments.

[0047] First type of embodiment: Combination Figures 1(a) to 1(e) It is known that when the metal dopant is a metal rod 20, the metal rod 20 is dispersed in the substrate 10 along a preset direction; specifically, the preset direction is that the length direction of the metal rod 20 is consistent with the stretching direction when the substrate 10 is stretched, so that the composite master material can be stretched to obtain a polarizer, and it helps to improve the control accuracy of the transmission axis of the polarizer.

[0048] As a further example, the aspect ratio of the metal rod 20 is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100. It is understood that the aspect ratio of the stretched metal rod 20 determines the working bandwidth of the polarizer. The stretching can be performed multiple times, therefore the range of the aspect ratio before stretching can be relatively wide, and the final aspect ratio can be controlled within the range required for the polarizer's operation.

[0049] As an example, the diameter of the metal rod 20 ranges from A. 10 -5 mm~A 10 -1 mm; preferably, the diameter of the metal rod 20 is in the range of A. 10 -3 mm~A 10 -2 mm, where A is the thickness or diameter of the substrate 10, and the unit of the above values ​​is mm.

[0050] It is understood that the aforementioned substrate 10 can be a block (such as...) Figures 1(a) to 1(d) (as shown) or cylindrical rod shape (as shown in Figure 1(e)).

[0051] Further, as an example, the metal rods 20 may be of the same size (as shown in Figures 1(a), 1(b), and 1(e)) or not entirely the same size (as shown in Figures 1(c) and 1(d)); the metal rods 20 may be a single metal rod or a combination of multiple segmented metal rods (as shown in Figures 1(a) and 1(e)). It is understood that the size of the metal rods 20 determines the working bandwidth, and the number of rods oriented in the same direction determines the extinction ratio. When the metal rods 20 are of the same size, the working bandwidth of the polarizer is narrow; when the metal rods 20 are not entirely the same size, the working bandwidth of the polarizer is wide. Those skilled in the art can design the size and number of metal rods 20 according to actual needs to ultimately obtain a polarizer with corresponding performance.

[0052] It should be further noted that the scattering of light by the metal in the substrate leads to a decrease in transmittance. Considering the overall transmittance of the material, the proportion of metal rods (which can be called metal wires when the metal rods are thin) in the base material should not exceed 20% Wt, preferably less than 10% Wt. Since the metal element is incorporated into the substrate, the reduction depth does not need to be considered compared to metal halides. Therefore, the content of metal wires / rods in the substrate can be lower than the metal content in metal halide-containing substrates produced by conventional stretching reduction melting.

[0053] The preparation method of the above-mentioned polarizer composite matrix can be found in [reference needed]. Figure 2 As shown, it includes the following steps: Step S101: Provide a substrate; the substrate is a stretchable material with a light transmittance greater than a preset light transmittance; In some embodiments, the substrate material can be conventional glass, and the glass system is not limited, such as borosilicate glass, soda-lime glass, aluminosilicate glass, etc. High softening point glass and high transmittance glass are preferred, with a softening point Tg of 600℃~1500℃ and a transmittance T≥80%. The metal wire / rod can be gold, silver, copper, or other metals, with silver and copper being preferred, selected in combination with the softening point and transmittance of the glass substrate and the melting point of the metal rod material.

[0054] Step S102: Provide a plurality of metal rods; the materials of the metal rods and the substrate are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal rods are in a semi-molten or molten state; Considering overall uniformity, the metal wires / rods need to be uniformly dispersed within the glass substrate. Furthermore, the distance between the metal rods along their minor axis can be determined by the relevant extinction ratio requirements, the weight percentage of the metal rods, the material of the metal rods, and the design of the composite substrate. It should be noted that when a relatively high extinction ratio is desired for the polarizer, this can be achieved by controlling the distance between adjacent metal rods; the smaller the distance between the metal rods, the lower the extinction ratio. The preferred distance between the metal rods is <A / 2mm, where A represents the thickness of the substrate in mm. Simultaneously, arranging the metal rods along the same direction (the stretching direction) and pre-orienting them along that direction helps improve the control accuracy of the polarizer's transmission axis.

[0055] Step S103: A plurality of dispersed through holes are formed in the substrate; Preferably, the above-mentioned methods for creating through holes include, but are not limited to: drilling, acid etching, chemical reaction or dissolution.

[0056] Step S105: Place the plurality of metal rods into the corresponding through holes to obtain the polarizer composite base material.

[0057] It should be noted that assembling a metal rod nested within a glass substrate is not limited to mechanical connections such as drilling, acid etching of the holes, and then threading the rod through, to obtain the polarizer composite material. This assembly method is relatively simple. It can also be combined through chemical reactions or dissolution, but since the glass substrate and the metal rod are two different types of materials, this method is more difficult.

[0058] Specifically, the dimensions of the metal rods and the composite base material can be matched and adjusted according to actual needs and circumstances. The width or outer diameter of the composite base material can be adjusted according to the stretching equipment. Considering the efficiency of single-batch preparation, for bulk composite base materials, the width is preferably greater than 180mm, and for cylindrical rod-shaped base materials, the outer diameter is preferably greater than 150mm. The length of the base material is adjusted according to the size of the stretching tower; theoretically, the longer the length, the higher the efficiency of single-batch preparation. In addition, the thickness of the base material is limited. If the thickness of the base material is Amm, A is preferably ≤20mm. Currently, the polarizers used in free-space optical isolators are generally 0.2mm thick, but considering processing losses, they are generally stretched to much greater than 0.2mm. Therefore, metal rods with different outer diameter specifications within this range can be selected for assembly based on the original base material thickness. Metal rods with different outer diameters, combined with stretching control, will produce metal rods with different length-to-diameter ratios, which helps to broaden the working bandwidth of the polarizer.

[0059] Since the final product needs to be stretched into nanorods with different aspect ratios, it can also be segmented in advance during the assembly of the parent material and the metal rod. It can be divided into multiple segments of the same specification (outer diameter of the metal rod / wire) or multiple segments of different outer diameters of the metal rod. However, it is more difficult to operate when assembling different outer diameters. It is preferable to use multiple segments of the same specification of metal rods, and the length direction of the metal rods is not limited.

[0060] Second type of embodiment: In some further extended embodiments, based on the above... Figures 1(a) to 1(e) In the illustrated embodiment, the metal rod 20 can be replaced by a metal-containing composite rod, such as... Figures 3(a) to 3(f) As shown, the aforementioned metal composite rod includes: at least one set of nested composite structures; each set of composite structures includes several sub-metal rods 22 and a pre-defined substrate 23 enclosing the sub-metal rods 22, and a core rod 21 is provided in the center of the innermost composite structure. See [reference needed] Figures 3(a) to 3(c) As shown, when the core rod 21 is not provided in the middle of the innermost composite structure, the structure can be seen in Figure 3(f).

[0061] The materials of the pre-designed substrate and the mandrel are the same as those of the substrate mentioned above.

[0062] More preferably, the metal composite rod includes a core rod 21 and a plurality of sub-metal rods 22 embedded inside the core rod, as shown in Figures 3(d) and 3(e).

[0063] Specifically, when there are multiple nested composite structures, in Figures 3(c) and 3(f), 231 is the preset substrate for the encapsulated metal rod in the first layer composite structure, 232 is the preset substrate for the encapsulated metal rod in the second layer composite structure, and 233 is the preset substrate for the encapsulated metal rod in the third layer composite structure.

[0064] It should be noted that when a metal composite rod is used instead of a metal rod, the distribution of the sub-metal rod in the substrate will be more dispersed and uniform, and the performance of the corresponding polarizer will be more uniform.

[0065] It is understood that the aforementioned metal-containing composite rod can be stretched and then inserted into the substrate. The stretching can be done once or multiple times. Since the number of stretching operations of the polarizer when using the metal-containing composite rod is greater than the number of stretching operations of the composite base material using the metal rod 20, the aspect ratio range of the sub-metal rod 22 used in the metal-containing composite rod is wider than the aspect ratio range of the metal rod 20 in the aforementioned embodiment. Subsequently, the polarizer with the corresponding performance can be obtained by sequentially stretching the base material and the composite base material multiple times.

[0066] As a further example, when the metal dopant is a metal composite rod, the sub-metal rods 22 are dispersed in the metal composite rod along a preset direction, wherein the preset direction is the same as the length direction of the sub-metal rods 22 and the stretching direction when the substrate 10 is stretched.

[0067] In one example, the diameter of the sub-metal rod 22 ranges from A. 10 -4 mm~A 10 1 mm; preferably, the diameter range of the sub-metal rod 22 is A. 10 -2 mm~A 10 -1 mm, where A is the thickness or diameter of the substrate 10, and the unit of the value is mm; And / or the weight percentage of the sub-metal rod in the composite base material is less than 20%; And / or the aspect ratio of the sub-metal rod is greater than or equal to 1.5; preferably, the aspect ratio is in the range of 2 to 100.

[0068] Furthermore, it can be understood that the distance of the sub-metal rod along the minor axis can be determined by the relevant extinction ratio requirements, the weight ratio of the sub-metal rod, the material of the sub-metal rod, and the design of the composite base material.

[0069] Same as above Figures 1(a) to 1(e) In the embodiments shown, when the metal dopant is a metal composite rod, the dimensions of the sub-metal rods may be the same or not completely the same; the sub-metal rod may be a whole sub-metal rod or a combination of multiple segmented metal rods.

[0070] In some embodiments, considering the uniformity of the sub-metal rod within the metal-containing composite rod, a multi-level nested assembly is preferred. The outer diameter of the core rod is not less than the size of the metal rod, and the wall thickness of the sleeve is not less than the size of the sub-metal rod. Without considering operational complexity, the assembly can be followed by stretching, and the stretched metal-containing composite rod can replace the above method. Figures 1(a) to 1(e) The metal rods in the glass matrix are then assembled and repeated to improve the uniformity of the metal distribution in the glass matrix.

[0071] It should be noted that the metal rods in the polarizer typically need to be nanoscale nanorods (nano refers to the size of the metal rod, such as diameter and / or length). When using a metal-containing composite rod, the sub-metal rod 22 will obviously be thinner than the metal rod 20. When stretching the composite parent material into a polarization structure, the sub-metal rod 22 will be easier to stretch into a nanoscale metal rod. Therefore, the above solution has certain advantages.

[0072] The preparation method of the above-mentioned polarizer composite matrix can be found in [reference needed]. Figure 4 As shown, it includes the following steps: Step S201: Provide a substrate; the substrate is a stretchable material with a light transmittance greater than a preset light transmittance; Step S202: Provide a plurality of metal-containing composite rods; the metal-containing composite rods include: at least one set of composite structures nested within each other; each set of composite structures includes several sub-metal rods and a preset substrate enclosing the sub-metal rods; preferably, a core rod is provided in the middle of the innermost composite structure; the preset substrate and the core rod are made of the same material as the substrate; more preferably, the substrate is made of glass; or, the metal-containing composite rod includes: a core rod and several sub-metal rods embedded inside the core rod, the core rod being made of the same material as the substrate; more preferably, the substrate is made of glass; The mass percentage of the sub-metal rod in the metal-containing composite rod is less than 50%. It should be noted that when the metal-containing composite rod is composed of a sub-metal rod, a core rod, and a pre-defined substrate encapsulating the sub-metal rod, when the diameter of the metal-containing composite rod is comparable to that of the metal rod, the diameter of the sub-metal rod inside is smaller than that of the metal rod, making it easier to stretch. When using a metal-containing composite rod, the sub-metal rod inside is thinner. When stretching the composite parent material into a polarization structure, the thinner sub-metal rod will be easier to stretch into a nanorod, making it easier to prepare a polarizer.

[0073] If the mass ratio of the sub-metal rod in the aforementioned metal-containing dopant is too large, then the aforementioned metal-containing dopant is not suitable for being stretched alone. By controlling the mass ratio of the sub-metal rod within a suitable range, it can be stretched to a suitable size before the metal-containing dopant is placed into the substrate, and then placed into the substrate. When the metal-containing composite rod is placed after stretching, the number of stretching times required to prepare the polarizer using the metal-containing composite rod is more than the number of stretching times required for the composite base material using the metal rod. Therefore, the range of the aspect ratio of the sub-metal rod used in the metal-containing composite rod can be wider than the range of the aspect ratio of the metal rod in the aforementioned embodiment, and it is easier to prepare the polarizer.

[0074] Step S203: A plurality of dispersed through holes are formed in the substrate; Step S204: Insert the plurality of metal-containing composite rods into the corresponding through holes to obtain the polarizer composite master material.

[0075] Third type of embodiment: Referring to Figures 5(a) and 5(b), when the metal dopant is a metal ball 30, the metal ball can be a nano-metal ball; preferably, the diameter of the metal ball is in the range of 5 nm to 500 nm; and / or the metal ball is a solid ball or a hollow ball; and / or the size of the metal balls is the same (as shown in Figure 5(a)) or not exactly the same (as shown in Figure 5(b)); and / or the metal balls are dispersed in the pores 40 of the substrate in units of individual metal balls and / or in units of nano-metal ball assemblies.

[0076] In one embodiment, the preparation method of the above-mentioned composite base material can be as follows: The substrate and metal spheres are bonded by an intermediary material. For example, porous glass (with macropores that can be pores with a diameter of more than 100 nm) can be prepared first by sol-gel, adding pore-forming agents, organic foam, foaming method, etc. Then, metal powder is dissolved in an organic solvent, the porous glass is immersed in the organic solvent containing metal powder, and then heated and dried to make the organic solvent evaporate, finally obtaining the above-mentioned composite substrate containing metal dopants as metal spheres.

[0077] It should be noted that the above preparation method is a relatively conventional method, and those skilled in the art can also choose other methods to prepare the product according to the actual situation and technical level. This application does not limit the specific methods used in this embodiment.

[0078] Understandably, to reduce the scaling ratio during stretching, nanospheres, preferably made of silver, gold, or copper, can be incorporated into the substrate. The scattering of light by metals in the glass matrix leads to a decrease in transmittance. Considering the overall transmittance of the material, the weight percentage of the metal spheres in the substrate should not exceed 20% Wt, more preferably not exceeding 10% Wt. Considering the overall transmittance, the particle size of the nanospheres should not be too large, preferably ≤500nm. Since the stretching process involves thermal growth, spherical particles ≤100nm are more preferred. For overall uniformity, the metal spheres need to be uniformly dispersed in the glass matrix. The metal nanosphere powder fills the reserved spaces. To extend the bandwidth, within the preferred ≤100nm spherical particle range, nanospheres of different sizes can be combined and added. During filling, either the entire substrate can be filled, or a portion of the nanosphere powder can be filled at certain intervals, with the gaps filled with the glass substrate. The length and width of the substrate are adjusted according to the stretching equipment, and are not considered in relation to the substrate dimensions. The thickness of the base material is limited, preferably ≤20mm.

[0079] Fourth type of embodiment: See appendix Figure 6 When the metal dopant is metal particle 50, the metal particle 50 is a nano-metal particle; and / or nano-metal spheres are dispersed in the substrate as a single nano-metal particle and / or as a combination of multiple nano-metal particles.

[0080] It should be noted that this scheme mainly involves directly doping the substrate with metal, and controlling the appropriate and uniform doping is the key challenge. Doping can be achieved through ion beam sputtering deposition and high-energy ion beam implantation. Ion beam sputtering provides the target clusters, and the high-energy ion beam implants the sputtered metal clusters into the glass substrate. Considering the limited depth of ion beam implantation, ion beam implantation can be performed separately on the front side 61 and the back side 62 of the substrate.

[0081] The preparation method of the above-mentioned polarizer composite matrix is ​​described in [reference needed]. Figure 7 As shown, it includes the following steps: Step S301: Provide a substrate; the substrate is a stretchable material with a light transmittance greater than a preset light transmittance; Step S302, provide a metal target; the materials of the metal target and the substrate are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range that it can be stretched, the metal material corresponding to the metal target is in a semi-molten or molten state; Step S303: Metal particles from a metal target are injected into the substrate using ion beam sputtering deposition and ion beam implantation to obtain a polarizer composite master material.

[0082] Further preferably, due to limitations in the implantation effect, the base glass can be relatively thin, with a thickness preferably in the range of 0.01mm to 5mm. Specifically, the energy of the high-energy particle beam is preferably ≥10MeV, and considering the uniformity of the entire glass sheet, a large-size high-energy particle source is preferred. Metal particles such as silver / gold / copper are provided through a high-purity target material. Under a negative pressure environment of 0.01Pa to 1Pa, the target material is bombarded by an ion beam, causing the target material clusters to be ablated. The target material clusters are then implanted into the glass matrix under the impact of the high-energy ion beam. Full-area implantation can be performed, or selective implantation can be performed by using a photomask. When using a photomask, the implantation area can be as small as 0.01mm. 2 ~10mm 2 The injection area spacing can be controlled between 0.01Amm and 5Amm, where A represents the thickness of the base glass in mm. Single-sided injection is followed by double-sided injection; silver / gold / copper is the preferred target material.

[0083] It is understood that, based on the composite master material provided in the first to fourth embodiments described above, stretching it can yield the corresponding polarization structure; then, a simple post-processing of the polarization structure can be performed to obtain a polarizer.

[0084] Preferably, in conjunction with the above embodiments, after the polarizer composite master material provided in the above embodiments is applied, the composite master material is stretched to obtain the relevant polarization structure. Stretching the composite master material allows for control of its internal microstructure and adjustment of the material size to approximate the product size (primarily controlling the thickness direction; the wider the width, the larger the prepared material size and the higher the utilization rate). The stretching equipment mainly consists of a stretching tower, a stretching furnace, a feeding unit, a discharging unit, and a size detection unit. The stretching tower primarily provides overall structural support and reserves space for the stretching operation. Preferably, it extends longitudinally along the direction of gravity, ensuring that the stretching direction aligns with the direction of gravity.

[0085] More preferably, such as Figure 8 As shown, the stretching furnace can be divided into three areas based on the temperature field distribution: the feeding zone 80, the stretching zone 81, and the discharging zone 82. The overall temperature distribution shows that the stretching zone 81 has the highest temperature, while the temperatures at both ends are lower. Each area has its own independent heating / cooling and temperature measurement control system. The stretching furnace control system, along with the feeding and discharging unit control systems, are unified into a control cabinet and controlled by a single controller. The feeding unit is mainly responsible for supplying raw materials (rods / sheets of glass) into the furnace along the stretching direction, controlling product dimensions, and preventing breakage due to excessive stretching. The discharging unit is mainly responsible for pulling the stretched product to the required specifications out of the high-temperature stretching zone, while ensuring that the nanorods are stretched in the same direction. Stretching has stringent requirements for temperature and viscosity; the lower the temperature control accuracy, the better, within ±3℃.

[0086] It should be noted that, due to the increased softening point range of the stretched substrate (600℃~1500℃), the corresponding viscosity range for stretching is 10. 2 mooring~10 13 Furthermore, tensile tension is a key parameter for controlling the microstructure. The applied tension range is 10MPa to 300MPa, and the tension is adjusted according to the size of the stretched material within this range. As the tension increases, the aspect ratio increases. Due to the tendency of metallic materials to spherize under the influence of surface tension, the aspect ratio exhibits shrinkage. At this point, a high discharge speed can reduce shrinkage; therefore, a discharge speed greater than 10mm / min is preferred. However, excessively high discharge speeds result in poor stretching stability. Considering stability, the discharge speed should not exceed 1000mm / min.

[0087] For the first type of embodiment, a tensile test is performed within a certain temperature / viscosity range, wherein the preferred viscosity range in the tensile region is 10. 4 mooring~10 13For the stretching process, the metal rod is preferably stretched in a semi-molten state, with the stretching direction preferably vertically downwards along the direction of gravity. To improve product quality, an inert gas (nitrogen, argon, etc.) is circulated in the furnace for protection during stretching. By adjusting the stretching parameters, the tensile force is >10MPa, and the feed / discharge / material speed is matched and set according to the output size. During stretching, the metal rod in the substrate gradually thins under the action of tensile force. As the scaling ratio increases, the composite base material is thinned. Under the extrusion of the metal rod by the deformation of the substrate, the metal rod / wire breaks into multiple segments. At the same time, the metal rod / wire is stretched to the nanoscale, ultimately forming nanorods. Several nanorod segments are on the same straight line (vertically downwards along the direction of gravity). The aspect ratio refers to the ratio of the long end L to the short end W of the stretched nanorod. Different aspect ratios correspond to different working wavelengths, from the visible light band to the communication band. The aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0088] In one example, a schematic diagram of the stretched microstructure is shown below. Figure 9 As shown, 100 represents nanorods and 200 represents the stretched substrate. The stretched product is already a semi-finished product, requiring only post-processing before it can be sold.

[0089] Specifically, in some embodiments, the post-processing of the above-mentioned product may include: processing and coating the stretched sample. Processing mainly involves cutting the sample to the required size using a dicing machine and controlling surface quality such as flatness and parallelism using a grinding and polishing machine. The processing and grinding and polishing steps can be interchanged, and generally, processing is performed first, followed by grinding and polishing. The processed product is the finished product. Since this step is relatively mature, it will not be described in detail. Similarly, coating is mainly used to improve the transmittance of the product. For products like optical isolators, the insertion loss of the overall device needs to be considered. Therefore, the raw materials for the isolator, polarizers and Faraday films, need to be coated. Since the refractive index of the adhesive and the refractive index of the polarizer are close, the polarizer only needs to be coated on one side facing the air. The coating process is relatively mature, and it will also not be described in detail.

[0090] For the second type of embodiment, For the second type of embodiment, the tensile test is performed in the same manner as in the first type of embodiment, within a certain temperature / viscosity range, wherein the preferred viscosity range in the tensile region is 10. 4 mooring~10 13For the stretching process, the metal rod is preferably stretched in a semi-molten state, with the stretching direction preferably vertically downward along the direction of gravity. To improve product quality, an inert gas (nitrogen, argon, etc.) is circulated in the furnace for protection during stretching. By controlling the stretching parameters, the tensile force is >10MPa, and the feed / discharge / material speed is matched and set according to the output size. During stretching, the sub-metal rod in the substrate gradually thins under the action of tensile force. As the scaling ratio increases, the composite base material is thinned. Under the extrusion of the sub-metal rod by the deformation of the substrate, the sub-metal rod / wire breaks into multiple segments. At the same time, the sub-metal rod / wire is stretched to the nanoscale, ultimately forming nanorods. Several nanorod segments are on the same straight line (vertically downward along the direction of gravity). The aspect ratio refers to the ratio of the long end L to the short end W of the stretched nanorod. Different aspect ratios correspond to different working wavelengths, from the visible light band to the communication band. The aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0091] Specifically, the post-processing of the product is the same as in the first type of embodiment.

[0092] For the third type of embodiment, a tensile test is conducted within a specific temperature / viscosity range. Unlike the first and second types of embodiments, the spherical nano-metal particles have a larger specific surface area; for example, the specific surface area of ​​silver metal spheres is greater than that of silver chloride spheres. Therefore, higher requirements are placed on the tensile viscosity range and tensile force. The preferred viscosity range in the tensile region is 10. 4 mooring~10 11 For the stretching process, the metal spheres are preferably stretched in a near-molten state, with the stretching direction preferably vertically downwards along the direction of gravity. To improve product quality, an inert gas (nitrogen, argon, etc.) is circulated in the furnace for protection during stretching. By controlling the stretching parameters, the stretching force is preferably >30 MPa, and the feed / discharge / material speed is matched and set according to the output size. During stretching, the nanospheres in the substrate gradually thin under the action of tensile force, and the composite matrix is ​​thinned. Under the extrusion and tensile force of the metal spheres caused by the deformation of the substrate, nanorods are formed. The aspect ratio refers to the ratio of the long end L to the short end W of the stretched nanorod. Different aspect ratios correspond to different working wavelengths, from the visible light band to the communication band. The aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0093] Specifically, the post-processing of the product is the same as in the first type of embodiment.

[0094] For the fourth type of embodiment, a tensile test was conducted within a certain temperature / viscosity range. Due to the incorporation of nano-metal particles, similar to the third type of embodiment incorporating nano-metal spheres, the preferred viscosity range for the tensile region is 10. 4 mooring~10 11For the stretching process, the metal particles are preferably stretched in a near-molten state, with the stretching direction preferably vertically downwards along the direction of gravity. To improve product quality, an inert gas (nitrogen, argon, etc.) is circulated in the furnace for protection during stretching. By controlling the stretching parameters, the stretching force is preferably >30 MPa, and the feed / discharge / material speed is matched and set according to the output size. During stretching, the nano-metal particles in the substrate are gradually thinned under the action of tensile force, and the composite matrix is ​​thinned. Under the extrusion and tensile force of the substrate deformation on the metal particles, nanorods are formed. The aspect ratio refers to the ratio of the long end L to the short end W of the stretched nanorod. Different aspect ratios correspond to different working wavelengths, from the visible light band to the communication band. The aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0095] Furthermore, it is understood that, in contrast to the main problems existing in the preparation of polarizing glass sheets using the existing stretching reduction method, and the advantages of the solution provided in the embodiments of this application, the following summary can be made: 1. The existing mainstream stretching reduction method for preparing polarizers has many preparation steps, complicated process, high power consumption, long preparation cycle and low preparation efficiency. In contrast, the present application obtains polarizers by stretching the above-mentioned new polarizer composite master material, which has a simple process, low power consumption, short preparation cycle and high efficiency.

[0096] 2. In the stretching reduction method, the melting process often uses borosilicate glass as the formulation component, which limits the choice of glass substrate. Furthermore, it is difficult to prepare high-quality microcrystalline glass with excellent comprehensive properties such as high transmittance and high uniformity, and the control of the microcrystalline introduction ratio and particle size is challenging. In this application, the substrate only needs to be a material with high light transmittance and a softening point matching the half-melting point or melting point of the metal to prepare the polarizer. This allows for a wider range of substrate choices, and no reduction reaction is required. The aspect ratio of the nanorods can be controlled simply by adjusting the size of the metal dopant, making the size of the nanorods in the polarizer more controllable.

[0097] 3. The reduction process in the stretching reduction method involves the participation of reducing gas hydrogen under high temperature and pressure, posing a certain degree of danger. Furthermore, considering economic efficiency and metal particle scattering, overall reduction is not performed during reduction, resulting in a sandwich structure with two reduced sides and an unreduced middle. When the thicknesses of the two reduced sides are inconsistent, stress can easily occur. This application eliminates the need for a stretching reduction reaction, avoiding the risks of the reaction. Moreover, the simultaneous stretching of the metal dopants in the entire composite substrate allows for more controllable and uniform preparation of the polarizer, avoiding the stress generation found in existing technologies.

[0098] 4. Existing stretching reduction techniques have been reported, which reduce silver halides to silver particles, resulting in volume reduction and micropores in the glass substrate, potentially affecting long-term reliability. This application eliminates the need for a reduction reaction after stretching, significantly improving the long-term reliability of polarizer fabrication and use.

[0099] 5. The high extinction ratio performance of samples prepared by the stretching reduction method has limited working bandwidth; the currently reported bandwidth for a single polarizer is approximately 380 nm. In this application, by controlling the size of the metal dopant, its size is kept within a relatively wide range, which helps to broaden and control the working bandwidth of the polarizer.

[0100] It should be understood that expressions such as “comprising” and “may include” used in this application indicate the existence of the disclosed functions, operations, or constituent elements, and do not limit one or more additional functions, operations, and constituent elements. In this application, terms such as “comprising” and / or “having” are to be interpreted as indicating a particular characteristic, number, operation, constituent element, component, or combination thereof, but not to exclude the existence or possibility of adding one or more other characteristics, numbers, operations, constituent elements, components, or combinations thereof.

[0101] Furthermore, in this application, the expression "and / or" includes any and all combinations of the associated listed words. For example, the expression "A and / or B" may include A, may include B, or may include both A and B.

[0102] In the description of the embodiments of this application, it should be noted that, unless otherwise explicitly specified and limited, the term "connection" should be interpreted broadly. For example, "connection" can be a detachable connection or a non-detachable connection; it can be a direct connection or an indirect connection through an intermediate medium. "Fixed connection" refers to a connection where the relative positional relationship remains unchanged after connection. "Rotary connection" refers to a connection where the components can rotate relative to each other after connection. "Sliding connection" refers to a connection where the components can slide relative to each other after connection. The directional terms mentioned in the embodiments of this application, such as "top," "bottom," "inner," "outer," "left," and "right," are only for reference to the directions in the accompanying drawings. Therefore, the directional terms used are for better and clearer explanation and understanding of the embodiments of this application, and are not intended to indicate or imply that the device or component referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0103] Furthermore, the mathematical concepts mentioned in the embodiments of this application, such as symmetry, equality, parallelism, and perpendicularity, are limitations specific to the current technological level, rather than absolute and strict mathematical definitions. Slight deviations are permissible; approximations of symmetry, equality, parallelism, and perpendicularity are all acceptable. For example, "A and B are parallel" means that A and B are parallel or approximately parallel, and the angle between A and B can be between 0 and 10 degrees. "A and B are perpendicular" means that A and B are perpendicular or approximately perpendicular, and the angle between A and B can be between 80 and 100 degrees.

[0104] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for stretching a polarizing sheet, characterized in that, The polarizer composite base material includes: a substrate and a metal dopant, wherein the metal dopant is uniformly dispersed in the substrate; wherein the metal dopant includes at least one of a metal rod and a metal composite rod; the metal composite rod includes a sub-metal rod; When stretching the polarizer composite base material, the viscosity range of the base material is controlled to be 10. 2 mooring~10 13 The applied tensile force is controlled within the range of 10MPa to 300MPa, and the discharge speed is controlled within the range of 10mm / min to 1000mm / min. When the viscosity of the substrate is within its stretchable viscosity range, the metal material in the metal dopant is in a semi-molten or molten state. Under the extrusion action generated by the deformation of the substrate, the metal material in the metal dopant is stretched and thinned, and the metal material may break.

2. The stretching method for the polarizer as described in claim 1, characterized in that, The substrate is provided with a plurality of through holes, and at least one metal dopant is placed in each through hole; The metal dopant is placed into the substrate through the multiple through holes to obtain a composite base material; the substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range that allows it to be stretched by a stretching device containing a stretching furnace, the metal material in the metal dopant is in a semi-molten or molten state.

3. The stretching method for the polarizer as described in claim 2, characterized in that, When the metal dopant is a metal rod or a metal composite rod, the insertion is performed by drilling; the metal composite rod is inserted into the substrate by drilling after being stretched; and holes are drilled inside the substrate along the stretching direction of the substrate.

4. The method for stretching a polarizer as described in claim 1, characterized in that, The metal material in the metal dopant accounts for less than 20% of the weight of the polarizer composite matrix; the weight percentage ranges from 0.05% to 10%.

5. The method for stretching a polarizer as described in claim 1, characterized in that, The diameter of the metal rod is in the range of A×10. -5 mm~A×10 -1 mm, where A is the thickness or diameter of the substrate, and the unit of the value is mm; The diameter of the sub-metal rod is in the range of A×10. -4 mm~A×10 1 mm.

6. The method for stretching a polarizer as described in claim 1, characterized in that, The dimensions of the metal dopants in the substrate may be the same or not completely the same; and / or the aspect ratio of the metal rod is greater than or equal to 1.5; the aspect ratio of the sub-metal rod is greater than or equal to 1.

5.

7. The method for stretching a polarizer as described in claim 1, characterized in that, The metal-containing composite rod comprises: at least one set of nested composite structures; each set of composite structures includes several sub-metal rods and a preset substrate enclosing the sub-metal rods; a core rod is disposed in the center of the innermost composite structure; the preset substrate and the core rod are made of the same material as the substrate; the substrate is made of glass; or... The metal-containing composite rod comprises: at least one set of nested composite structures; each set of composite structures includes several sub-metal rods and a preset substrate enclosing the sub-metal rods; the innermost composite structure does not have a core rod in its center; the preset substrate is the same as the substrate; the material of the substrate is glass; or... The metal-containing composite rod includes a core rod and several sub-metal rods embedded inside the core rod, wherein the core rod is made of the same material as the substrate.

8. The method for stretching a polarizer as described in claim 1, characterized in that, The sub-metal rod accounts for less than 50% of the mass of the metal-containing composite rod. The softening point of the substrate is in the range of 600℃ to 1500℃.

Citation Information

Patent Citations

  • Production of polarizer and apparatus for production

    JP1995301710A

  • Polarizing element and its production

    JP1997043429A

  • Polarizer and its production

    JP2000249834A